Exit, Voice, Loyalty and Neglect as Student Responses to Dissatisfaction: An Act Frequency Approach - Mahaffey, Tom; Neut, Dean; Taylor, Alison (Canadian Journal of Higher Education, 1991)
An important task in higher education is the provision of an abstract theoretical model capable of integrating various student responses to dissatisfaction. Drawing upon recent work in the social sciences, we propose exit, voice, loyalty and neglect (EVLN) as a parsimonious means of understanding the relationships among the different responses to dissatisfaction. We use an act frequency approach to develop and validate the EVLN constructs as a preliminary first step toward future predictive theory.